2018
DOI: 10.1158/1078-0432.ccr-17-3571
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bromodomain and Extra-Terminal (BET) Family Proteins in Castration-Resistant Prostate Cancer (CRPC)

Abstract: Welti et al; Targeting BET family proteins in CRPC 2 Statement of Translational RelevanceAdvanced prostate cancer invariably progresses to lethal castration resistant prostate cancer (CRPC). Resistance to current androgen receptor (AR) targeting therapies is associated with the development of AR aberrations including the constitutively active AR splice variant 7 (AR-V7). Currently, no clinically available therapies effectively inhibit aberrant AR signaling. BRD4, a bromodomain and extraterminal (BET) family pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 50 publications
4
99
0
Order By: Relevance
“…Moreover, high BRD2 expression in primary tumors was associated with shorter PC-specific survival . More recently, the nuclear BRD4 protein level was confirmed to increase following castration resistance in longitudinally matched tumor samples collected pre and post treatment (Welti et al 2018). We also found that high expression of ATAD2 was positively associated with biochemical recurrence on a cohort of 10,000 patients .…”
Section: Bromodomain-containing Proteins and Chromatin Reprogramming supporting
confidence: 63%
“…Moreover, high BRD2 expression in primary tumors was associated with shorter PC-specific survival . More recently, the nuclear BRD4 protein level was confirmed to increase following castration resistance in longitudinally matched tumor samples collected pre and post treatment (Welti et al 2018). We also found that high expression of ATAD2 was positively associated with biochemical recurrence on a cohort of 10,000 patients .…”
Section: Bromodomain-containing Proteins and Chromatin Reprogramming supporting
confidence: 63%
“…Transcriptional signatures from intermediate adenocarcinoma patients overlapped with datasets from neuroendocrine prostate cancer patients, suggesting that in the context of retained AR function, tumors can also activate lineage plasticity networks to evade ADT without shutting down AR expression. Evidence of this exists where enzalutamideresistant preclinical models with AR expression have shown benefit from disruption of bromo-and extraterminal domain (BET) bromodomain proteins by BET inhibitors (14,15). Overall, BET inhibitors enhanced efficacy and reversed resistance to AR antagonists.…”
mentioning
confidence: 99%
“…Epigenetic drugs targeting the BET family of chromatin readers and transcriptional regulators, such as BRD4, are also in clinical development. Pre-clinical studies have shown that drugs targeting BRD4 disrupt its recruitment to chromatin sites bound by AR, suppress signaling, and, alone or in combination with ARPIs, demonstrate anti-tumour activity (Asangani et al 2014, Welti et al 2018. This is due, in part,to the requirement of BRD4 activity to mediate chromatin accessibility and AR transcriptional reprogramming during prostate cancer progression (Urbanucci et al 2017).…”
Section: Targeting Epigenetic and Transcriptional Regulators In Nepcmentioning
confidence: 99%